Análisis comparativo de programas infantiles en medios públicos y comunitarios desde la perspectiva de la interculturalidad - Candelejo Alcarraz, Karen Ivonne (2018)
The purpose of the researching was to establish differences and similarities of children's content between public and community media, through a study case of intercultural programs "Wawakuna, and “sueños de los libros”. This is take into count to children and the aim is to examine the strategies that each uses to capture the importance of multiculturalism in its contents. In this sense, this project aims to study an comparative analysis of children's programs of public and community media in terms of multiculturalism from Educa TV studio and TV Micc in order to identify each communication used elements by production of their content. The methodology used is qualitative, descriptive level. The technique that was applied is observation, given that gathering reliable information. That could go without getting involved in the job area; this investigation needed the maximum attention about the observed space. To do this, it was done the respective observation sheets, where the corresponding data was recorded. Likewise, to reinforce the investigation, an agenda of questions was made, as support material to execute a structured interview to the producers of the investigated media, wich explained in detail everything about their programs and strategies that use to develop content. Among the main results that was found: spreading the theme of interculturality in these media differs in that in public media there is a greater orientation toward mestizo visions, while in the community media, the vision is mostly indigenous. Among the most important conclusions is that, although with limitations, the intercultural approach is better conceived in community media than in the public, which allows identifying weaknesses in the level of public policies in the field of communication intercultural.